Global health systems comparing strategies for delivering health services - Lovett-Scott, Margie; Prather, Faith (Jones & Bartlett Learning, 2014)
In this book the authors aim to demonstrate what can be learned from healthcare systems around the world, to help improve the US system, and how healthcare leaders should shift their focus from management to leadership.